Presepsi Warga terhadap Covid 19 - Ahmad Jarkasih (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2021)
The purpose of this study was to obtain information on people's perceptions of Covid 19. The study used qualitative methods to obtain information on people's perceptions of Covid 19. This study was limited to a sample size of 5 respondents who were in Cilodong Village, Cilodong District, Depok City. The results of the research are that. COVID-19 is a dangerous and contagious disease. The existence of COVID-19 in the world economic sector has decreased as well as in Indonesia, even many companies have gone out of business and laid off their employees because they cannot pay. Teaching and learning activities become obstructed. They always worry about traveling or working, therefore work is limited. From this, every citizen has positive expectations that every activity will return to normal.